Political and Social Participation of Teachers: Conceptual Distinctions in the Academic Literature on Teacher Associationism - Ortiz-Mallegas, Sebastián; Torres-Sánchez, Mónica; Barruel, Daniela; Brignardello, Sofía (Revista Electrónica Educare, 2025)
Background. Today’s societies demand from their citizens an active involvement in socio-political scenarios. In this context, education appears as a fertile space for learning socio-political participation, with teachers as a key agent in this dynamization. However, like other citizens, teachers face the challenges of learning to participate. A particularly relevant domain of this learning process is that of associative spaces, which are currently being challenged to envision alternative forms of teacher collectivization. Purpose. this article aims to understand the relationships established in the scientific body between teachers’ socio-political participation and teachers’ associationism. Method. Based on a systematic review of the literature in high impact scientific databases (Wos and Scopus), 46 empirical articles on teachers’ political and social participation and teacher associationism were analysed, between 2011 and 2021. Results. The analyses show a significant number of articles that refer to participation as a competence of teachers, requiring their performance in different schools’ contexts and on different topics; even though participation is a continuous learning process that is not limited to university instances, but rather is channelled in teacher associations. Conclusions. We discuss the implications of this mode of participation for teachers and the link with teacher associations in a global context that has built a global discourse on the role of teachers in the teaching profession.